Injustice 2 - Taylor, Tom, 1978-; Miller, Mike S.; Redondo, Bruno, 1981-; DC Comics, Inc.; NetherRealm Studios; WB Games (Firm); Warner Bros. Interactive Entertainment (Burbank, CA Warner Bros. Interactive Entertainment, 2017)
"Power up and build the ultimate version of your favorite DC legends in Injustice 2. With a massive selection of DC Super Heroes and Super-Villains, Injustice 2 allows you to equip every iconic character with unique and powerful gear earned throughout the game. Experience an unprecedented level of control over how your favorite characters look, how they fight, and how they develop across a huge variety of game modes. This is your super Hero. Your Journey. Your Injustice."--provided by Amazon.com.
Video game.
1-2 players; 2-10 Xbox Live players.
"Additional storage, hardware, broadband (ISP fees apply), Microsoft Account, and Xbox Live may be required for setup, some updates and features, including retention of some gameplay settings and information"--Container.
Manual available online.
Accompanying material may vary; some copies do not include booklet featuring comic art.
Included in accompanying booklet: Injustice 2 : the origin of Supergirl / writer: Tom Taylor ; artist: Mike S. Miller and Injustice 2 character art / art and colors by Bruno Redondo.
Keywords: DC Comics, Inc -- Computer games; Supervillains -- Computer games; Superheroes; Comic strip characters; Hand-to-hand fighting; Imaginary wars and battles; Computer games; Video games; Xbox One (Video Game Console).; Xbox video games; Xbox One video games; Multiple player video games